Luteinizing hormone receptor knockout mouse: What has it taught us? - Huhtaniemi, Ilpo T. (Wiley, 2026)
Luteinizing hormone (LH), along with its agonist choriongonadotropin (hCG) in humans, is the key hormone responsible for the tropic regulation of the gonadal function. LH and hCG act through their cognate receptor, the luteinizing hormone/choriongonadotropin receptor (LHCGR; more appropriately LHR in rodents lacking CG), located in the testis in Leydig cells and in the ovary in theca, luteal, and luteinizing granulosa cells. Low levels in LHCGR are also expressed in numerous extragonadal sites. Hypogonadism is observed in humans expressing inactivating mutations in the LHβ-subunit (LHB)and LHCGR genes, confirming the crucial role of LH and LHCGR in gonadal development and function. Unraveling of the LHR structure and the advent of gene manipulation techniques enabled the production of mouse models with inactivated LHR function, that is, the LHR knockout (LuRKO) mouse, some 20 years ago. This mouse model has thereafter been instrumental in various experimental settings, alone or combined with other genetically modified mouse models, in providing novel, and in some cases unexpected, details about the LH/LHR function. We will review here the salient findings of these studies.